Atribut Kualitas Kopi Arabika pada Tiga Ketinggian Tempat Di Kabupaten Garut - Juniaty Towaha; Eko Heri Purwanto; Handi Supriadi (Jurnal Tanaman Industri dan Penyegar, 2015)
Garut is one of producing areas of Arabica coffee that has a distinctive flavor and aroma, which could potentially be a specialty coffee. The objective of this study was to determine the quality attributes of Arabica coffee grown at three different altitudes. The experiment was conducted at smallholder coffee plantations in Garut, West Java Province from April to October 2014. Arabica coffee that ripen physiologically (red color), which were used as sample in this study, were harvested from three different growing altitudes: A = 1,200 m above sea level (Simpang Village, Tarajuk Sub-District), B = 1,400 m above sea level (Margamulya Village, Cikandang Sub-District), and C = 1,600 m above sea level (Kramatwangi Village, Cisurupan Sub-District). Coffee berries were subsequently processed using wet processing procedure. Green beans resulted from those wet processing were then subjected to analysis of protein, caffeine, lipid, and ash content (conducted at Integrated Laboratory of Indonesian Industrial and Berverage Crops Research Institute) as well as organoleptic testing (cupping test) (performed at Indonesian Coffee and Cocoa Research Institute). Flavor attributes, including aroma, flavor, body, acidity, aftertaste, sweetness, balance, clean cup, uniformity, and overall were assessed. The results showed that the total score of Arabica coffee flavor that grow at three different altitudes was 81.25–83.00 (meet the criteria as a specialty coffee). Arabica coffee that grows at an altitude of 1,600 m above sea level have the highest value of protein, caffeine, fat, and ash content as well as total score of flavors with a character of spicy, strong fragrance, and chocolaty.